PKM OSENG LANGUAGE SAVING THROUGH INVENTORY IN THE LARGE INDONESIAN DICTIONARY - Agus Mursidi (International Jurnal of Education Schoolars, 2021)
In the design results of the Oseng vocabulary inventory that has been carried out by the Koord Team. KKLP of Dictionary and Terminology, and Coords. KKLP for the Protection and Modernization of the East Java Language Center. The number of words generated from the field is 730 words that must be verified. The eligibility of words that must be verified is very decisive to be submitted in word validation to the East Java Language Center of the Ministry of Education and Culture of Indonesia, the target audience because of a request from the Chairperson of the East Java Province Language Center at the Faculty of Teacher Training and Education, PGRI Banyuwangi University, which requires resource persons for verification of fluent vocabulary. totaling 730 words. The word was verified by 4 people from the Oseng tribe who were represented by the chairman of the Balambangan Arts Council, Drs. Hasan Basri, M.Pd, Oseng Language Institute Minhajul Qowwim, SS., 2 academician at PGRI Banywuangi University is a descendant of Oseng Dr. Agus Mursidi, M.Pd end Nur hasibin, M.Pd. 5 people from the Coord Team. KKLP of Dictionary and Terminology, Researcher Puspa Ruriana, M.Hum with members Adista Nur Primantari, M.A. and Yuyun Kartini, S.S and 2 of the language instructors. The activity was carried out in 5 days at the Luminor hotel from 23-25 May 2022 with a letter of assignment starting 22-26 May 2022. From the results of the verification that has been carried out by the Team, there are 3% of words that are deleted because they are already in the big Indonesian dictionary, 2% of words are repeated, 10% of words that must be verified to vocabulary sources, 85% are verified words that are eligible to be submitted validation to the Indonesian Language Center of the Ministry of Education and Culture.